Women, leadership and violent extremism: A potential security risk? - Aurélie Wertz; Dorcas Mbuvi (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2020)
This paper examines an important and overlooked subject area. Women's role in extremist organisations is neglected in general, and the question of their tactical leadership in these settings is poorly understood. Without specific focus on particular extremist movements or ideologies and, to advance understanding and spur critical discussions around female leadership in violent extremism, we propose three conceptual models. The first details key drivers that plausibly facilitate the emergence of female extremist leaders. The second discusses six possible female leadership styles and the third touches on female spheres of influence in violent extremism. The paper provides preliminary explorative insights on a neglected topic while offering opportunities for further research.
Keywords: D02; D74; F52; H12; J16; Z18; 330; women; gender; violent extremism; leadership styles; counter-terrorism; security threats